Performance enhancement of shape memory poly(aryl ether ketone) via photodimerization of pendant anthracene units. (15th January 2020) - Gu, Yiyang; Ru, Chunyu; Zhao, Zhen; Chao, Danming; Liu, Xincai
Graphical abstract: We synthesize novel poly(aryl ether ketone)s bearing flexible alkyl segments and pendant anthracene groups through nucleophilic copolycondensation coupled with post-polymerization functionalization. After the photodimerization of pendant anthracene units, the resultant polymers exhibit enhanced shape memory performance with satisfying shape fixity ratio and shape recovery ratio, attributed to their photocrosslinked polymeric network architecture. Highlights: PAEKs bearing flexible alkyl segments and pendant anthracene groups were prepared. Crosslinked polymer structure was prepared by photodimerization of anthracene units. The polymers show satisfying shape memory behavior due to their network architecture. Abstract: Shape memory polymers have attracted much attention due to their promising applications in biomedicine, textiles, aerospace et al. Here, novel poly(aryl ether ketone)s bearing flexible alkyl segments and pendant anthracene groups were synthesized via nucleophilic copolycondensation coupled with post-polymerization functionalization. Their chemical structure, thermostability and mechanical properties were characterized through Fourier Transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, thermal gravimetric analysis and dynamic mechanical analysis. The soft-rigid alternative segment structure endows these poly(aryl ether ketone)s with promising shape memory properties. After the photodimerization of pendant anthracene units, the resultant polymers exhibit enhanced shape memory performance in terms of satisfying shape fixity ratio and high shape recovery ratio, attributed to their photocrosslinked polymeric network architecture. This shape memory polymer with reversible photodimerization holds great promise for a deep understanding of the mechanism and future applications.